Toxicity assessment of ethanolic Moringa oleifera leaf extract (Mole) using zebrafish (Danio rerio) model - Sarchio, Seri Narti Edayu; Daud, Nur Liyana; Ismail, Elysha Nur; Shamsi, Suhaili; Abdul Zahid, Intan Nurzulaikha (Universiti Putra Malaysia Press, 2025)
Moringa oleifera, locally known as ‘Kelor’ in Malay, is a medicinal plant valued in Malaysia and other countries. It is renowned for its therapeutic bioactive compounds and offers significant health benefits, including anticancer and anti-inflammatory properties. However, the toxicity profile of ethanolic M. oleifera leaf extract (MOLE) has not been well explored. This study aims to assess the toxicity profile of MOLE using a zebrafish (Danio rerio) model. Zebrafish embryos were subjected to MOLE (n ≥ 15; 24h post-fertilisation (hpf)) at a concentration of 5-1000 μg/mL, and the survival rate, hatching rate, heart rate, and morphological development of zebrafish embryos were monitored daily for up to 72 h. Embryo media was used as a control. MOLE treatment was shown to be safe at concentrations ≤ 400 μg/mL with LC50 values of 1186 ±7 μg/mL, 560.1 ±7 μg/mL, and 445.1 ± 7 μg/mL at 24, 48, and 72 h post-treatment, respectively. A significant mortality rate and low heartbeat were recorded in embryos exposed to > 800 μg/mL across the three time points. MOLE did not affect the hatching rate. Although there was a significant difference observed in embryos treated with > 800 μg/mL at 72 h post-treatment, these were not attributable to MOLE effects, as the embryos had died before hatching. Scoliosis was predominantly observed in embryos subjected to MOLE concentrations ranging from 25 to 200 μg/mL. The present data demonstrated that MOLE exhibited concentration- and time-dependent toxicities. Further studies are needed to identify the effective concentrations of MOLE for therapeutic application in in vitro and in vivo models.